Determination of JW5473 in Rat Plasma by UPLC-MS/MS and its Application to Pharmacokinetic Study of JW5473 - Kim, Tae Kon (Drug Research, 2019)
A sensitive method for quantitation of JW5473 in rat plasma has been established using ultra performance liquid chromatography-electrospray ionization tandem mass spectrometry (UPLC-ESI/MS/MS). Tramadol was used as an internal standard. JW5473 and internal standard in plasma sample was extracted using acetonitrile (protein precipitation). A centrifuged upper layer was then evaporated and reconstituted with the mobile phase of 0.5% formic acid-acetonitrile (40:60, v/v). The reconstituted samples were injected into a C18 reversed-phase column. Using MS/MS in the multiple reaction monitoring (MRM) mode, JW5473 and tramadol were detected without severe interference from rat plasma matrix. JW5473 produced a protonated precursor ion ([M+H]+) at m/z 432.3 and a corresponding product ion at m/z 114.4. And the internal standard produced a protonated precursor ion ([M+H]+) at m/z 264.4 and a corresponding product ion at m/z 58.1. Detection of JW5473 in human plasma by the UPLC-ESI/MS/MS method was accurate and precise with a quantitation limit of 1.0 ng/mL. The validation, reproducibility, stability, and recovery of the method were evaluated. The method has been successfully applied to pharmacokinetic studies of JW5473 in rat plasma. Pharmacokinetic parameters of JW5473 was evaluated after intravenous (i. v.; at doses of 15 mg/kg) and oral (p.o.; at doses of 30 mg/kg) administration of JW5473 in rats. After p.o. administration (30 mg/kg) of JW5473, F (Fraction absorbed) value was approximately 70.5%.
Keywords: JW5473; tramadol; UPLC-ESI/MS/MS; bioavailability; rats